2021
DOI: 10.3847/1538-4357/ac079f
|View full text |Cite
|
Sign up to set email alerts
|

Near-Sun Switchback Boundaries: Dissipation with Solar Distance

Abstract: The most surprising result from the first solar encounters by the Parker Solar Probe (PSP) is the large amount of brief magnetic field reversals often referred to as switchbacks. Switchbacks have previously been observed further downstream in the solar wind by spacecraft such as Helios 2 at 62 R s from the Sun. However, these observations lack a distinct proton temperature increase detected inside switchbacks by PSP, implying that they are evolving ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Thus, there appear to be two classes of MHs near the Alfvén critical surface: switchback boundary associated (like those in Figure 1) and boundary unassociated (Figure 3). The superposed epoch analysis studies performed previously (Farrell et al 2020;Rasca et al 2021) clearly indicate that the alignment of the MHs at the switchback boundary is not accidental-and that they occur in direct association with the boundary. In other words, while MHs can be found at other locations in the solar wind, there is clearly the formation of MHs in association with the boundaries of the switchbacks, where enhanced electron flows are also present (Rasca et al 2022).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, there appear to be two classes of MHs near the Alfvén critical surface: switchback boundary associated (like those in Figure 1) and boundary unassociated (Figure 3). The superposed epoch analysis studies performed previously (Farrell et al 2020;Rasca et al 2021) clearly indicate that the alignment of the MHs at the switchback boundary is not accidental-and that they occur in direct association with the boundary. In other words, while MHs can be found at other locations in the solar wind, there is clearly the formation of MHs in association with the boundaries of the switchbacks, where enhanced electron flows are also present (Rasca et al 2022).…”
Section: Introductionmentioning
confidence: 78%
“…Figure 1 shows the magnetic field and plasma wave activity for an individual switchback detected during the E1 encounter (Rasca et al 2021). In this particular example, the switchback boundary-centered in time-is very abrupt and distinct: there is nearly a full rotation of the magnetic field (from inward-tooutward pointing) occurring in only a few seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Switchbacks are now considered part of the solar wind character in close to the Sun. Figure 1 shows an example of one of these switchback events detected during E1 (from Rasca et al 2021). The Alfvénicity of switchbacks is illustrated here with the abrupt change in B r (associated with a B-field rotation and constant-magnitude |B|) and a corresponding increase in solar wind speed, V r inside the switchback event.…”
Section: Introductionmentioning
confidence: 99%
“…During the close-encounter periods, PSP is moving primarily longitudinally in the Carrington rotation system, crossing magnetic field lines that are connected to a set of underlying supergranulation structures and thereby giving rise to the observation of periodically occurring patches of switchbacks (see Figure 6 of Fargette et al 2021 and Figure 9 of Bale et al 2021). Rasca et al (2021) found that the switchbacks dissipated with radial distance from the Sun. They reported that the abrupt change in B r and V r , ΔB r and ΔV r that occurs at switchback boundaries is strong in close to the Sun (<0 R S ), but progressively decreases in value with R S .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the folded magnetic field structures will stretch to radial as the solar wind propagates in the interplanetary space, thus there must be some mechanisms to help avoid the relaxations of the S-shape structures of switchbacks. Rasca et al (2021) predict the switchbacks may survive until around 60 R S based on the evolutions of the magnetic field and speed changes in the boundaries of switchbacks. Some studies indicate that current sheets exist in the switchback boundaries (Farrell et al 2020;Krasnoselskikh et al 2020;Martinović et al 2021), which implies the presence of strong electric fields in the layers to keep the system quasi-stable.…”
Section: Introductionmentioning
confidence: 99%